ANTIBODIES TO HUMAN COMPLEMENT FACTOR C2B AND METHODS OF USE (2022)
Provided are antibodies and antigen-binding fragments thereof that bind specifically to human complement factor C2 and are capable of inhibiting activation of the classical and lectin pathways of the complement system. The antibodies and antigen-binding fragment exhibit improved manufacturability, pharmacokinetics, and antigen sweeping. Also provided are pharmaceutical compositions comprising the antibodies and antigen-binding fragments, nucleic acids and vectors encoding the antibodies and antigen-binding fragments, host cells comprising the nucleic acids or vectors, and methods of making and using the antibodies and antigen-binding fragments. The antibodies and antigen-binding fragments can be used to inhibit the classical pathway of complement activation in a subject, e.g., a human. The antibodies and antigen-binding fragments can also be used to inhibit the lectin pathway of complement activation in a subject, e.g., a human.